2022
DOI: 10.1155/2022/5841017
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impact of Wushu Sports Health on College Students’ Mental Health

Abstract: At the current university stage, university students are subjected to a variety of pressures such as role change adaptation pressure, study and life pressure, emotional pressure, economic pressure, employment pressure, and interpersonal pressure, which seriously affect their physical and mental health. Students with poor psychological tolerance may develop psychological disorders and, in serious cases, may even lead to mental illness. The results of the study indicated that 17%–20.23% of university students ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Based on a large sample population, covering more than 9 thousand students from 35 colleges in several regions of Jiangsu Province, and using valid diagnostic materials, the conclusions of the study were formulated: measures to develop physical activity will reduce dependence on mobile phones and have a positive impact on the psychological capital and social adaptation of students. This is an important conclusion for the transformation of the mechanisms of social adaptation of first-year students at the university at the stage of entering into academic activity [5,6,7].…”
Section: Introductionmentioning
confidence: 79%
“…Based on a large sample population, covering more than 9 thousand students from 35 colleges in several regions of Jiangsu Province, and using valid diagnostic materials, the conclusions of the study were formulated: measures to develop physical activity will reduce dependence on mobile phones and have a positive impact on the psychological capital and social adaptation of students. This is an important conclusion for the transformation of the mechanisms of social adaptation of first-year students at the university at the stage of entering into academic activity [5,6,7].…”
Section: Introductionmentioning
confidence: 79%
“…Due to the degree of heterogeneity observed in the study design, and outcome indices, meta-analysis was considered impractical. 15 studies mainly used a quantitative research design (6,12,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). All 15 articles received a score between 4 and 5, indicating their high methodological quality.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The average score representing medical college students' knowledge of coping with public health emergencies only ranged from 52.13 ± 8.17 to 79.43 ± 10.40 (the total score was uniformly converted to 100 points). The percentage representing the passing rate of medical college students in the assessment of coping with public health emergencies, or the awareness/mastery/accuracy rate of knowledge related to public health emergencies, ranged from 32.55 to 72.38% (6,12,25,33) (Table 3). These studies demonstrated that respondents generally have a low ability to deal with public health emergencies.…”
Section: Cognitive Status Of Medical College Students In Response To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is also an underlying social dimension associated with the exercise, which indirectly contributes to the larger social context. (Sun et al, 2022) Mindfulness and training discipline may help athletes. Martial arts athletes can improve their performance by cultivating a disciplined mentality and incorporating mindfulness methods to stay focused, manage stress, and control emotions.…”
Section: Introductionmentioning
confidence: 99%